2015
DOI: 10.1016/j.jmrt.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the substitutional elements on the microstructure of the Ti-15Mo-Zr and Ti-15Zr-Mo systems alloys

Abstract: j m a t e r r e s t e c h n o l . 2 0 1 5;4(2):180-185 w w w . j m r t . c o m . b r Biomaterials Microstructure a b s t r a c t Titanium alloys have excellent biocompatibility, and combined with their low elastic modulus, become more efficient when applied in orthopedic prostheses. Samples of Ti-15Mo-Zr and Ti-15Zr-Mo system alloys were prepared using an arc-melting furnace with argon atmosphere. The chemical quantitative analysis was performed using an optical emission spectrometer with inductively coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 25 publications
(35 reference statements)
3
43
0
1
Order By: Relevance
“…The authors observed that with 6 wt% of molybdenum a small amount of α″ phase begins to form and above 9 wt% of molybdenum, a significant amount of β phase was present. It can be observed that the presence of β-stabilizer elements made zirconium a non-neutral element and pass to act on stabilizing β-phase in the alloy [11,15]. Peaks of α″ phase in Ti-20Zr-2.5Mo and presence of peaks from the β phase in Ti-20Zr-5Mo and Ti-20Zr-7.5Mo alloys are related to the action of zirconium, which together with another β-stabilizer element (in the case molybdenum), acts on β-transus temperature decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that with 6 wt% of molybdenum a small amount of α″ phase begins to form and above 9 wt% of molybdenum, a significant amount of β phase was present. It can be observed that the presence of β-stabilizer elements made zirconium a non-neutral element and pass to act on stabilizing β-phase in the alloy [11,15]. Peaks of α″ phase in Ti-20Zr-2.5Mo and presence of peaks from the β phase in Ti-20Zr-5Mo and Ti-20Zr-7.5Mo alloys are related to the action of zirconium, which together with another β-stabilizer element (in the case molybdenum), acts on β-transus temperature decreases.…”
Section: Resultsmentioning
confidence: 99%
“…This element is considered neutral to form alloys with titanium. However, it decreases the initial temperature of martensitic α′ transformation [10], and in the presence of another β stabilizer element, it has β stabilizer actuation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of Mo can decrease Young's modulus and improve the corrosion resistance of the material [12,13]. In previous studies, we have found low Young's modulus (60-80 GPa), high tribocorrosion resistance, and good cell viability in Ti-15Zr-Mo alloys [9,[14][15][16]. In particular, the Ti-15Zr-15Mo alloy displayed the best potential for biomedical application.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, alloying these two elements can lead to an improvement in the corrosion and mechanical behaviour of the alloy [89,90]. Any increase of molybdenum may lead to a decrease in β-transus temperature, and Mo has a higher β stabilizing impact on the TZM than Zr [91].…”
Section: Chemical Compositionmentioning
confidence: 99%